2023
DOI: 10.3389/fonc.2023.1142081
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for extensive-stage small-cell lung cancer: current landscape and future perspectives

Abstract: Small-cell lung cancer (SCLC) is a fatal subtype of lung cancer characterized by high aggressiveness, poor prognosis, and limited treatment options. For the first time in more than three decades, it has been demonstrated that the addition of immunotherapy to chemotherapy improved the survival of patients with extensive-stage SCLC, thereby immunotherapy plus chemotherapy established a new standard of first-line treatment. However, it is important to improve the curative effect of immunotherapy on SCLC and ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The findings of this study suggest that the inclusion of Atezolizumab alongside chemotherapy as a primary treatment for ES-SCLC led to a modest increase of 2 months in OS and 0.9 months in progression-free survival (PFS) compared to chemotherapy alone. This trial is a significant milestone, as it provides the initial evidence of the therapeutic advantage associated with PD-L1 inhibitors in individuals diagnosed with ES-SCLC, albeit with only a modest effect size [ 57 ]. The randomized distribution of patients without the knowledge of drug target levels might be a reason for the limited clinical response observed in IMpower133 [ 10 , 11 , 12 , 13 ].…”
Section: Immunotherapy In Sclcmentioning
confidence: 99%
“…The findings of this study suggest that the inclusion of Atezolizumab alongside chemotherapy as a primary treatment for ES-SCLC led to a modest increase of 2 months in OS and 0.9 months in progression-free survival (PFS) compared to chemotherapy alone. This trial is a significant milestone, as it provides the initial evidence of the therapeutic advantage associated with PD-L1 inhibitors in individuals diagnosed with ES-SCLC, albeit with only a modest effect size [ 57 ]. The randomized distribution of patients without the knowledge of drug target levels might be a reason for the limited clinical response observed in IMpower133 [ 10 , 11 , 12 , 13 ].…”
Section: Immunotherapy In Sclcmentioning
confidence: 99%
“…Most recently, a large number of studies have shown promising antitumor activity from first-line immunotherapy drugs plus platinum-based chemotherapy. This has resulted in a significant improvement in SCLC patients with extensive disease in terms of diseasefree survival (PFS) and overall survival (OS) versus chemotherapy alone [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Stage IV SCLC is an advanced and aggressive form of lung cancer characterized by rapid growth, early metastasis, treatment resistance and disease recurrence, resulting in a poor prognosis for patients ( 3 ). Platinum-etoposide chemotherapy was the standard first-line treatment for extensive-stage SCLC (ES-SCLC) for several decades; however, the need for additional treatment strategies remained ( 3 , 4 ). After decades of little progress, immune checkpoint inhibitors (ICI) revolutionized the treatment landscape, leading to a new standard of care in the first-line setting ( 3 - 6 ).…”
mentioning
confidence: 99%